2014
DOI: 10.1371/journal.pone.0098450
|View full text |Cite
|
Sign up to set email alerts
|

Independent Component Analysis and Decision Trees for ECG Holter Recording De-Noising

Abstract: We have developed a method focusing on ECG signal de-noising using Independent component analysis (ICA). This approach combines JADE source separation and binary decision tree for identification and subsequent ECG noise removal. In order to to test the efficiency of this method comparison to standard filtering a wavelet- based de-noising method was used. Freely data available at Physionet medical data storage were evaluated. Evaluation criteria was root mean square error (RMSE) between original ECG and filtere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A large number of methods to deal with noise and/or artefacts from ECG signals have been developed, such as adaptive Filters [2,3], Independent Component Analysis (ICA) [4], Empirical Mode Decomposition (EMD) [5], adaptive Fourier decomposition [6], Savitzky-Golay filter [7], threshold method for high frequency noise detection [8], Kalman filters [9], Bayesian filter framework [10], wavelet technique [11], clustering of morphological features [12], and Neural Networks [13]. Very recent attempts include arrhythmia heart classification using different Deep Learning (DL) models [14] and QRS characteristics identification using Support Vector Machines (SVM) [15].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of methods to deal with noise and/or artefacts from ECG signals have been developed, such as adaptive Filters [2,3], Independent Component Analysis (ICA) [4], Empirical Mode Decomposition (EMD) [5], adaptive Fourier decomposition [6], Savitzky-Golay filter [7], threshold method for high frequency noise detection [8], Kalman filters [9], Bayesian filter framework [10], wavelet technique [11], clustering of morphological features [12], and Neural Networks [13]. Very recent attempts include arrhythmia heart classification using different Deep Learning (DL) models [14] and QRS characteristics identification using Support Vector Machines (SVM) [15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this limitation, a wavelet adaptive filter is proposed in [16]. Recently, various techniques have been proposed based on wavelet transforms [17]- [20], interpolation algorithms [21], sparse signal decomposition [22], principal component analysis [23], independent component analysis [24], and empirical mode decomposition (EMD) [25] method. EMD is computationally very demanding in comparison to the other techniques [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the suitability of the random subspace ensemble method for fMRI classification has been investigated [23]. It has previously been shown that decision trees were successfully used for variable selection and classification in fMRI brain activities [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%